2014
DOI: 10.5505/1304.7361.2014.15428
|View full text |Cite
|
Sign up to set email alerts
|

First Aid Knowledge of University Students in Poisoning Cases

Abstract: SUMMARYObjectivesPoisoning is a crucial public health problem which needs serious approach and response to treatment. In case of poisoning, proper first aid is lifesaving and application should be applied in every condition. This research was conducted in order to evaluate first aid knowledge of university students for poisoning.MethodsThe research was conducted between the dates of May 2013–June 2013 with the permission gained from the University Rectorship. The cohort of the research contained 4,560 students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…It should be remembered besides severe outcome as death, permanent disabilities because of amputation can occur after snake bites [17]. It has been determined that just 17% of students know accurate first aid for snake bites in a study with university students in Turkey [45]. A similar study that searched first aid recommendations for snake bites has found 54.1% of the pages include recommendations not matching with guidelines [22].…”
Section: Discussionmentioning
confidence: 99%
“…It should be remembered besides severe outcome as death, permanent disabilities because of amputation can occur after snake bites [17]. It has been determined that just 17% of students know accurate first aid for snake bites in a study with university students in Turkey [45]. A similar study that searched first aid recommendations for snake bites has found 54.1% of the pages include recommendations not matching with guidelines [22].…”
Section: Discussionmentioning
confidence: 99%
“…La investigación realizada con alumnos de una universidad de Medicina en Estambul demuestra, además, que los estudiantes que recibieron educación de primeros auxilios tuvieron un mejor desempeño, en cuanto a la identificación y la conducta en casos de envenenamiento, que el de los alumnos que no recibieron la educación sobre el tema [23].…”
Section: Discussionunclassified
“…Availability of such information could bring benefit to poison management control centres in planning preventive interventions to educate the community efficiently. A study by Goktas et al (2014) evaluated respondents' knowledge on the information regarding poisoning cases involving the household chemical products. It was mentioned that respondents' knowledge is affected by their health education background and level of awareness.…”
Section: Knowledgementioning
confidence: 99%